The labor market in Poland, 2000-2021 - Piotr Lewandowski; Iga Magda (IZA World of Labor, 2023)
In the early 2000s, Poland's unemployment rate reached 20%. That is now a distant memory, as employment has increased noticeably and the unemployment rate had dropped to 3.4% in 2021. The labor force participation of older workers increased following reforms aimed at prolonging careers. However, participation remains low compared to most developed countries and the reversal of the statutory retirement age in 2017 leaves Poland vulnerable to the effects of population aging. Rising immigration has eased the resulting labor shortages, but women, people with disabilities, and agricultural workers remain underemployed. During the Covid-19 pandemic the slowdown in economic growth and increase in unemployment were small.
Keywords: J3; J2; E24; J41; 330; wages; labor supply; unemployment; temporary contracts; Poland